Novel therapeutic targets in rheumatoid arthritis - Sakthiswary Rajalingham, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Rheumatoid arthritis (RA) is the most common chronic systemic autoimmune disease worldwide. Although incurable, there are available therapies to effectively control the disease activity and minimize the joint damage. Numerous cytokines, enzymes and other forms of proteins have been implicated in the disease process of RA. In general, pharmacological therapies in RA target cytokine pathways. Despite a wide variety of disease modifying antirheumatic drugs (DMARD), a significant proportion of patients remain refractory to the available therapies. Hence, the search for newer drugs with different modes of actions is an ongoing process. The present review aimed to explore novel therapeutic targets in RA based on data from the literature. Inhibitors of spleen tyrosine kinase, choline kinase, galectin 3 and hypoxia-inducible factor may have a promising role in thetreatment of RA. Besides, cell based therapies which may enhance the levels of systemic tristetraprolin could be beneficial in RA.